Epidemic outbreak control with hygiene practices from Islamic perspective: a conceptual framework / Zainab Hisham … [et al.] - Hisham, Zainab; Mustafa@Busu, Zanirah; Junoh, Noraini; Nik Wan, Nik Zam; Nik Din, Nik Muniyati; Muhammad Hashim, Nurhidayah; Yusoff, Zulkarnain (Kaizentrenovation Sdn Bhd, 2022)
Appreciation of personal hygiene is a foundation of faith that must be given attention by every Muslim. Hygiene is divided into two categories, namely external hygiene, and internal hygiene. The focus here is on external hygiene, which includes personal hygiene, clothing and the environment. Islam requires its believers to practice cleanliness in everything, whether in worship or outside of worship. Personal hygiene in worship is cleaning oneself, body, place before performing worship, by performing ablutions, istinja’, and cleansing the body, bathing. Specialized here is the obligatory bath (janabah). As for personal hygiene outside of worship, it includes cleaning the hands and mouth, and cleaning the teeth (siwak). The practice of this practice has been taught by the noble Prophet Rasulullah SAW since the beginning of Islam. Since the emergence of the COVID-19 infectious outbreak, new norms have been introduced by the World Health Organization (WHO). The Ministry of Health (MOH) advises the public to consistently maintain procedures to curb the spread of this dangerous epidemic. They set some guidelines for the community to practice in daily life. One of the recommended procedures is related to hygiene, which is to clean the hands and ensure that the hands are always clean. This is in parallel recommended by the teachings of Islam brought by the Prophet SAW. Therefore, every Muslim community must ensure personal hygiene is maintained as prescribed by Islam to prevent the spread of COVID-19. This study aims to outline personal hygiene according to the syariah that can be used as a practice in the life of the Muslim community. The results can be used as the main guide for the entire Malaysian community of various ages because it is a practical practice of a Muslim. This study uses a qualitative descriptive research approach to library research by referring to books, journals, articles, the internet, and so on. In addition, researchers conducted observational studies from previous research studies. Researchers also take and refer to the views of ulama muktabar. The results found are about understanding and appreciating the practice of hygiene recommended by religious law. Through this writing, the guidelines and procedures set by the Ministry of Health Malaysia (MOH) and daily practices that have been emphasized by the Prophet SAW must be considered in improving the practice of personal hygiene as the responsibility of a Muslim in facing this epidemic.